The governance imperative: The influence of effective governance in unlocking intrapreneurial potential for sustainable public value - Lucy T. Chamba; Ismael Tarirai (Africa’s Public Service Delivery & Performance Review)
Background: Environmental, Social, and Governance (ESG) practices are gaining traction, with a particular focus on State-Owned Enterprises (SOEs) and their contribution to sustainability. This study looks at how governance promotes intrapreneurship, a key capability for SOEs to achieve sustainability through public value creation.